IDENTITY PHENOMENON RESEARCH: THEORETICAL LEVEL - Кисельова, В. А. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2019)
Classical and modern theories of identity, such as E. Giddens concept of self-identity, social identity of I. Hoffmann, non-reflective identity of M. Foucault, the theory of recognition and social imaginary of C. Taylor, the concept of imaginary communities of B. Anderson, the theory of «using the Other» and the exclusive identity of I. Neumann are analyzed. As a result of the analysis, methodological benchmark principles for the conceptualization of identity phenomenonare defined. It is suggested to consider the phenomenon of identity as a multi-level construct, also, the principles of identity typology are developed. According to this typology, ontological (personal identity) and social (collective identity) dimensions of the phenomenon are distinguished. It is admitted that personal identity, in addition to being directly connected with emotions, is the result of an individual’s personal experience. Meanwhile collective identity is a phenomenon of a social level, mental awareness of the existence of a community that shares common for an individual interests/values. As types of personal identity, the reflective, when the individual asks himself «whom I relate to/ want to relate myselfto?», and non-reflective – the individual unconsciously reproduces certain practices, patterns of behavior –forms of the phenomenon are analyzed. Within the framework of collective identity, it is suggested to distinguish between identities according to the institutional level (regional/local or national/state), as well as according to the attributes of a social group (ethnic, racial, linguistic, gender, etc.). The attention is drawn to the further perspective of the social identity study precisely through the prism of the institutional level. In particular, the following research question is identified as an important aspect of the further research: how the features of the reproduction of certain formal and informal practices affect the formation and «renewal»/reconstitution of regional and national identities.